An analysis of workplace English speaking courses for university engineering students in the Kwara State of Nigeria - Solihu, Abdulateef; Abdul Latif @ Bapoo, Lilisuriani (GTA Press, 2020)
The globalization of world markets which has led to the hegemony of English language over other languages requires graduates from different fields of specialization to equip themselves with English communication skills to communicate effectively in local and international workplace contexts. This study was conducted to investigate the English speaking skills needed by engineering students in the Kwara states of Nigeria. A survey was carried out to compare how the respondents’ (undergraduate engineering students and industry workers in the Kwara State of Nigeria) self-rated their speaking interaction and production skills and to observe their perception of the importance of speaking interaction and production sub skills for workplace communication. The study concluded with suggestions for creating a better perception of the importance of English speaking skills among engineering students and creating a better workplace English curriculum so that students’ workplace speaking skills can be improved.